2021
DOI: 10.5334/tohm.651
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of Patient Home Videos in Movement Disorders

Abstract: Background: Numerous studies have shown the value of patient home video recordings within the field of epilepsy. Despite the growing influence of mobile technology and telemedicine, there is a paucity of studies examining the role of home videos in the diagnosis of movement disorders.Objective: To characterize the clinical value of patient home videos in a movement disorders practice. Methods:We performed a retrospective review from our video database over the past 10 years and identified 20 encounters where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Relatively fair inter-rater agreement has been identified among movement disorder specialists for the diagnosis of psychogenic jerks [ 80 ], as well as on the judgment between an organic or functional movement disorder based on video interpretation [ 81 ]. The differences in accuracy between phenomenologic and etiologic diagnostic assessments reflect the importance of the neurological history and complete neurological examination for the comprehensive clinical assessment [ 82 ]. On the other hand, telemedicine gives the opportunity for a more detailed observation of the patient at their homes or other environments, which could assist in the differential diagnosis of functional movement disorders.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Relatively fair inter-rater agreement has been identified among movement disorder specialists for the diagnosis of psychogenic jerks [ 80 ], as well as on the judgment between an organic or functional movement disorder based on video interpretation [ 81 ]. The differences in accuracy between phenomenologic and etiologic diagnostic assessments reflect the importance of the neurological history and complete neurological examination for the comprehensive clinical assessment [ 82 ]. On the other hand, telemedicine gives the opportunity for a more detailed observation of the patient at their homes or other environments, which could assist in the differential diagnosis of functional movement disorders.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In one small study looking at the value of home videos for movement disorders, it was shown that out of 20 home videos, 50% were determined to be of additional clinical value and in 62.4% of evaluations it was possible to identify the phenomenology from the home videos and were found to be consistent with the final diagnosis. In this respect, it is also important to note that video quality was a key determinant for identifying the correct phenomenology; videos rated as ‘poor quality’ had significantly lower odds of leading to a correct phenomenology ( Billnitzer & Jankovic, 2021 ).…”
Section: Videoconferencing and Assessments Via Video Systemsmentioning
confidence: 99%
“…Standardized video protocols have been established for clinical rating scales, such as the Unified Dyskinesia Rating Scale for Parkinson's disease (Goetz et al, 2008) and the Dyskinesia Impairment Scale (DIS) in dyskinetic cerebral palsy (CP) (Monbaliu et al, 2012). With the widespread use of smartphones, self-recorded home videos have also shown their clinical value (Billnitzer and Jankovic, 2021).…”
Section: Introductionmentioning
confidence: 99%